Inserção da máscara laríngea por enfermeiros: revisão integrativa da literatura. - Noronha Silva, Gabriela Cruz; Pires Bernardinelli, Fabiana Cristina; de Campos Pereira Silveira, Renata Cristina; Pedersoli, Cesar Eduardo; de Amorim, Gustavo Correa; Ribeiro Chavaglia, Suzel Regina (Revista Eletrônica de Enfermagem, 2022)
Objective: To identify evidence-based literature on the laryngeal mask airway insertion by nurses. Method: Integrative literature review conducted in November 2020, searched in the Cumulative Index to Nursing and Allied Health Literature, Cochrane, Excerpta Medica Database, Latin American and Caribbean Health Sciences Literature, US National Library of Medicine National Institutes Database Search of Health and Web of Science through the Rayyan Study Selection Program. Results: Eight out of the 1,156 studies identified met the inclusion criteria. Studies were categorized into first and second-generation devices. Conclusion: The use of a first and second-generation laryngeal mask airway by nurses is a recommended alternative for its speed, success and effectiveness in ensuring the advanced airway, especially in situations of cardiopulmonary arrest in adults. However, adverse effects of its use should be evaluated.